PENGARUH CURRENT RATIO DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA - Ida Yusnita (Gapenas Publisher, 2021)
This research aimed to determine the influence of: (1) Current ratio (2) Net Profit Margin And (3) Profit growth on PT. Unilever Indonesia Tbk The research period was 2009- 2019. This research was classified as ex post facto research, causal associative, and quantitative approach. The result of the research showed that: (1) Current ratio had no effect to Firm Value with regression with significance 0.159>0,05 and Current ratio variable t-count 1,1553 (2) Net Profit Margin had positive effect to Profit growth with significance 0,09 Net Profit Margin variable t-count 3,481 in 2009-2019 with F-count 3,299and significance 0,035The result of the adjusted R2 test in this study obtained a value of 0.068. This showed that the profit growth was influenced by current ratio and net profit margin of 68%,while the rest of 32% was influenced by other factors not examined in this study